COVID-19 Pandemic Impact on Sexually Transmitted Infection Testing in a College Setting - Marconi, Agustina M.; Falk-Hanson, Elizabeth C.; Crass, Megan E.; Campbell, Peter (Universidad y Salud, 2022)
Introduction: COVID-19 pandemic has had a great impact on health systems. Many non-urgent visits were done virtually to limit exposure risks. Objective: Assess the impact of the pandemic on STI (sexually transmitted infections) testing in a college health setting. Material and methods: Quantitative assessment of the number of STI tests done, positive rates and percentage of “compliance to follow-up” for diagnosed STI from March to December 2020 and its comparison with historical data (2015-2019) at the University Health Services, UW-Madison. Measurement: Observed (2020) vs expected (2015-2019) number of STI tests, positive rates and compliance to follow-up testing for STIs. Results: The 2020 period showed a significant decrease in the number of tests done and an increase of positive rate when compared to historical data for total sample and per sex. There was a decrease in the percentage of follow-up for the entire sample and for females and an increase for males. Conclusions: In accordance with national data, our analysis shows significant declines in STI testing and follow-up during 2020 compared to previous years and an increase in positivity rate. A higher positivity with lower number of tests is likely due to triaging patients, facilitating testing for those at highest risk.